Fludarabine, Cyclophosphamide, and Multiple-Dose Rituximab as Frontline Therapy for Chronic Lymphocytic Leukemia - Short, Nicholas J. (Cancer, 2015)
BACKGROUND: Fludarabine, cyclophosphamide and rituximab (FCR) results in durable responses in patients with previously untreated chronic lymphocytic leukemia (CLL). Previous reports suggest that in patients with relapsed CLL a dose-intensified rituximab regimen increases response rates compared to standard-dose rituximab. It is unknown whether rituximab intensification of the FCR regimen will result in improved response rates and patient outcomes in patients with previously untreated CLL. METHODS: We conducted a single-arm study to evaluate the safety and efficacy of a modified FCR regimen with multiple-dose rituximab (FCR3) in 65 patients with previously untreated CLL. Results were compared to an historical cohort treated with FCR. RESULTS: The overall response rate to FCR3 was 97%, with 75% of patients achieving a complete remission. Minimal residual disease negativity was achieved in 62% of patients by flow cytometry. Median time to progression (TTP) was 81 months, and median overall survival (OS) was not reached, with 58% of patients still alive at a median survivor follow-up of 9.7 years. Grade 3-4 neutropenia, grade 3-4 thrombocytopenia and major infection were observed with 45%, 5% and 1.9% of FCR3 courses, respectively. Therapy-related myelodysplastic syndrome (t-MDS) or acute myelogenous leukemia (t-AML) developed in 7 patients (11%) (P <0.01 compared to the historical FCR cohort). CONCLUSIONS: In patients with previously untreated CLL, FCR3 resulted in similar response rates, TTP and OS compared to a historical cohort of patients treated with FCR. FCR3 was associated with an increased incidence of t-MDS/AML.